The legal risks associated with trading in derivatives in a merchant bank - Terblanché, Janet René (University of Stellenbosch, 2006)
The research defines derivatives as private contracts, with future rights and obligations imposed on all parties, used to hedge or transfer risk, which derives value from an underlying asset price or index, which asset price or index may take on various forms. The nature of derivatives is that the instruments are intended to be risk management tools. The objectives of derivatives are either to hedge a risk, or to speculate. Derivatives may be classified by the manner in which they are traded, either over the counter (OTC) or on exchange. Alternatively, derivatives may be classified on the basis of structure and mechanisms, i.e. forwards, futures, options or swaps. Risk and risk management are defined in the third chapter with the focus on merchant banking. The nature of risk is that it is inherent in all activities. The nature of risk management is that it aims to ensure that the risks faced by the merchant bank are managed on a daily basis. The objective of risk management is to ensure that losses are minimised and the appropriate level of risk is taken in order to maximise profits. Risk may be classified as operational, operations, market, systemic, credit and legal risk. A comprehensive discussion of credit risk is presented, as it pertains to the legal risk in derivatives in a merchant bank. This includes insolvency, set-off, netting, credit derivatives and collateral. Legal risk is defined as the risk of loss primarily caused by legal unenforceability (i.e. a defective transaction, for instance a contract), legal liability (i.e. a claim) or failure to take legal steps to protect assets (e.g. intellectual property). The nature of legal risk is that it is caused by jurisdictional and other cross-border factors, inadequate documentation, the behaviour of financial institutions, a lack of internal controls, financial innovation or the inherent uncertainty of the law. The objectives of legal risk management in derivatives are to avoid the direct and indirect costs associated with legal risk materialising. This includes reputational damage. Derivatives attract specific legal risks due to the complexity of the instruments as well as the constant innovation in the market. There remains some legal uncertainty regarding derivatives in terms of gaming, wagering and gambling, as well as insurance. The relationship between risk and derivatives is that due to the complexity and constant innovation associated with derivatives, there are some inherent risks to trading in derivatives. It is therefore important to ensure that there is a vested risk management culture in the derivatives trading environment. Chapter four gives an overview of derivatives legislation in foreign jurisdictions and in South Africa. The contractual and documentation issues are discussed with reference to ad hoc agreements, master agreements and ISDA agreements. The practical implementation issues of master agreements and ad hoc agreements are also discussed. The recommendations are that legal risk management be approached in a similar manner to credit, market and other risk disciplines. A legal risk management policy needs to be developed and implemented. The second recommendation is that a derivative to manage the legal risk in derivatives be developed.

Legal risk and compliance risk in the banking industry in South Africa - Terblanché, Janet René (North-West University, 2013)
The Basel Committee on Banking Supervision has defined operational risk, legal risk and compliance risk. However, the definitions might not be adequate for countries with a hybrid legal system, such as South Africa. This study aims to provide a practical solution to the problems faced by countries with a hybrid legal system wishing to comply with the Basel Committee’s standards. It is argued that compliance, compliance risk and regulatory risk should all be viewed as constituent components of legal risk, and in turn necessarily also of operational risk in a hybrid legal system. Legal risk is a wide concept which includes all aspects of a legal system, while compliance risk is a narrower concept which only includes the codified aspects of a legal system. Legal risk therefore includes compliance risk. However, the opposite is not true as compliance risk does not include legal risk, and the two concepts are decidedly shown not to be synonymous in a mixed legal system.
Keywords: Basel Committee; Compliance; Compliance risk; Legal compliance; Legal risk; Operational risk; Regulatory compliance; Regulatory risk